Effectiveness of Compassion-based Treatment in Depression, Anxiety, and Aggression of Emergency Medical Workers with Covid-19 - Mohammad Soltani Delgosha; Shahram Vaziri; Fatemeh Shahabizadeh; Qasem Ahi; Ahmad Mansouri (Hamadan University of Medical Sciences, 2023)
Background and Objective: With the spread of Covid-19, emergency medical workers have suffered physical and mental problems that require therapeutic interventions. The present study aimed to determine the effectiveness of compassion-based treatment in depression, anxiety, and aggression of medical emergency workers with Covid-19. Materials and Methods: In this study, we adopted a quasi-experimental pretest-posttest control group design. The statistical population included emergency medical workers infected with Covid-19 in Mashhad in 2021. A total of 40 cases were selected as the sample using the available sampling method and were randomly assigned to two groups: experimental (n=20) and control (n=20). The compassion-based treatment was implemented in the form of eight 90-minute sessions once a week for the experimental group, and the control group did not receive any intervention. The participants were assessed in the pre-test and post-test stages according to Zigmond and Smith's (1983) depression and anxiety tests and Bass and Perry's (1992) aggression tests. The data were analyzed in SPSS software (version 26) using Covariance analysis. Results: According to the results of this research, compassion-based treatment had an effect on depression, anxiety, and aggression of medical emergency workers with Covid-19 (P< 0.001). Based on the eta square, this effect was 0.44 on depression, 0.39 on anxiety, and 0.52 on aggression. Conclusion: Therefore, it is suggested that counselors and therapists use the compassion-based treatment approach to reduce the psychological problems of emergency medical workers, especially during the Covid-19 crisis.